Investigation of Leisure Strategies of Sports Educated Students - Aslan, Huseyin; Imamoglu, Osman (Asian Journal of Education and Training, 2020)
In this study, it was aimed to investigate Leisure time strategies of sports educated students, who going to Fitness Centers. In addition to sports training, the effect of whether or not to compete as a contestant was also examined for Leisure Strategies. A total of 543 men on fitness centers filled up the Scala “Leisure Strategy Scale” before training. Independent t-test in paired comparisons and one-way analysis of variance (ANOVA) in multiple comparisons and LSD tests were used to determine the difference. A statistically significant difference was found in the leisure strategy subscales and total score according to the age category of University of students (p <0.05). In leisure friendship, the scores of 20 years and under and 21-23 age groups are higher than in the 24 years old and above age group in case of temporary coping and mood improvement. A significant difference was found in all subscales and total scale scores in comparison of leisure strategy subscale and total scores according to income (p <0.05).Conclusion: In addition to sports education, leisure strategies of university students doing sports in Fitness centers differ according to age category and income status. It has that whether or not participating in competitions in sports training students, who going fitness Center does not have a different effect in terms of leisure strategies. In terms of leisure strategies, this study is recommended to be done according to the status of being an amateur and professional athlete in sports-inclined students.